Rural Sustainability: Children’s Libraries As A Tool To Revive Rural Villages In China - Ferretto, Peter W. Ferretto; Lam, Man Yan; Liu, Ziwei (MAJ - Malaysia Architectural Journal, 2025)
Rapid decline of rural Chinese villages poses a significant concern, driven by phenomena such as village hollowing and industrialization, which result from the migration of the working populace seeking improved employment opportunities. As a result, these villages face the risk of cultural erosion, with only young children and elderly residents remaining amidst the transition. The replacement of traditional timber dwellings with concrete structures further accelerates the loss of cultural heritage which for centuries has been the identity of their culture. The Dong ethnic minority, constituting one of China's 56 ethnic groups, inhabits regions with a rich history dating back to the Tang Dynasty, encompassing more than three million people. This study focuses on two Dong villages situated in southwest Hunan Province, profoundly affected by this rural transformation. By implementing two architectural prototypes, the research endeavours to foster social resilience in these villages, aiming to preserve their cultural identity and advocate for the integration of social architecture paradigms within rural Chinese communities. The Gaobu Book House and Pingtan Book House, named after their respective villages, serve as multifunctional spaces catering to various community needs, including leisure for the elderly, communal gatherings, and experiential learning for children. The research delineates the comprehensive development process of these prototypes, encompassing problem identification, stakeholder engagement, fundraising efforts, architectural design, local carpentry collaboration and book provision. Through these initiatives, children in Gaobu and Pingtan villages are afforded opportunities for educational enrichment and cultural connection, thereby revitalizing the communities and reinforcing their sustainability within the rural landscape. When communities develop an affinity for their architectural structures, sustainability inherently ensues as it fosters feelings of pride and belonging.